Leadership Effectiveness in Nepalese Service Organizations - Upadhyay, Dipesh (Journal of Nepalese Business Studies, 2008)
Leadership is important for Nepalese managers today than ever due to globalization and increasing competition. The findings show leadership has near to moderate level of effectiveness in Nepal which means it is under-utilized as indicated by the variable taken for this study i.e. vision, empowerment, communication, task/relationship orientation and locus of control scales.The Journal of Nepalese Business Studies Vol. IV, No.1(2007) pp. 105-109